PEMANFAATAN UDARA BUANG EXHAUST FAN SEBAGAI PEMBANGKIT LISTRIK TENAGA BAYU DENGAN PENAMBAHAN WIND TUNNEL BERBASIS ATMEGA 2560 - Made Satria Tresnajaya; Cok Gede Indra Partha; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2020)
Energy needs from year to year has increased along with the increase of population,economic growth, and high energy consumption. Until now, the world still depends on fossilfuels, this causes the depletion of oil availability and also causes air pollution. As a developingcountry, many industries are running around us and also many new industries are growingevery day. Every industry generally has an exhaust fan to maintain the temperature of the workspace. This exhaust fan works to remove air from the inside out. This research uses exhaustfan exhaust by using a 2-blade turbine and the addition of a wind tunnel, which will latercompare the output between using a wind tunnel and without using a wind tunnel. In theresearch the use of exhaust fan exhaust air without using a wind tunnel to get an output of0,30625W while with the addition of wind tunnel output increased by 8,25% to 0,76176W.